Phytopathogenic bacteria associated with vegetable crops in the Tropics - Aumentado, Herbert Dustin R.; Guerrero, Jonathan Jaime G.; Balendres, Mark Angelo (Journal of Scientific Agriculture, 2025)
Vegetables are among the most important crops in Southeast Asian countries, including the Philippines. Bacterial pathogens are among the most important constraints in vegetable production, causing destructive diseases. This paper provides an overview of bacterial diseases of vegetable crops in the Philippines. Here, we focus on the pathogens associated with these diseases and highlight interventions done globally to mitigate the diseases’ impact on vegetable production. Phytopathogenic bacteria are associated with ten plant diseases in the Philippines. These are bacterial wilt (Ralstonia solanacearum species complex), bacterial soft rot (Pectobacterium carotovorum), bacterial leaf spot (Xanthomonas campestris pv. vesicatoria), black rot (Xanthomonas campestris pv. campestris), bacterial fruit blotch (Acidovorax avenae subsp. citrulli), angular leaf spot (Pseudomonas syringae pv. lachrymas), common scab (Streptomyces scabiei), bacterial speck (Pseudomonas syringae), bacterial canker (Clavibacter michiganensis), and tomato pith necrosis (Pseudomonas corrugata). Using pathogen-free seeds, field sanitation, removal of weeds and alternate hosts, immediate removal of infected plant parts, and regular disease monitoring can aid in minimizing losses due to bacterial diseases. Finally, critical areas for future research to increase the understanding of vegetable diseases in the country and improve their management strategies are briefly discussed.